After Thermopylae : the oath of Plataea and the end of the Graeco-Persian Wars - Cartledge, Paul (Emblems of antiquity., 2013)
The Battle of Plataea in 479 BCE is one of world history's unjustly neglected events. It decisively ended the threat of a Persian conquest of Greece. It involved tens of thousands of combatants, including the largest number of Greeks ever brought together in a common cause. For the Spartans, the driving force behind the Greek victory, the battle was sweet vengeance for their defeat at Thermopylae the year before. Why has this pivotal battle been so overlooked? In After Thermopylae, Paul Cartledge masterfully reopens one of the great puzzles of ancient Greece to discover, as much as possible, w.